Analisis Pengaruh Pengetahuan Kewirausahaan Terhadap Sikap dan Minat Berwirausaha Santri Pondok Pesantren Bintang Sembilan - Wahyudi, Indra; Wulandari, Sri; Suryani , Fitri Ayu (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Although many Islamic boarding schools have integrated entrepreneurship education into their curriculum, challenges remain in developing entrepreneurial attitudes and interests among students. Adequate entrepreneurial knowledge is expected to inspire students to develop positive attitudes and a strong interest in entrepreneurship. This study aims to examine the impact of entrepreneurial knowledge on the attitudes and interests of students at the Bintang Sembilan Islamic Boarding School. The methodology used was quantitative, with a descriptive research design. The study sample consisted of all active students in the 2023/2024 academic year who had participated in entrepreneurship training, totaling 38 respondents. Data collection was carried out using a Likert-scale questionnaire, which was then assessed for validity and reliability. The results of the validity test showed that all statement items were valid, while the reliability test confirmed that all variables were reliable. Data analysis was carried out using simple linear regression. The research findings indicate that entrepreneurial skills have a substantial impact on entrepreneurial attitudes. Entrepreneurial knowledge has a substantial impact on entrepreneurial interest. The research findings indicate that entrepreneurial knowledge positively and significantly influences students' attitudes and interests in entrepreneurship. This study recommends the importance of strengthening the entrepreneurship curriculum in Islamic boarding schools to foster character and a spirit of economic independence among students.